Application of optimal FrFT order for improving the azimuth resolution of range Doppler imaging algorithm. Issue 4 (19th February 2020) - Wang, Zhenli; Wang, Qun
Abstract : The traditional range Doppler (RD) imaging algorithm has become the most intuitive and classical method in synthetic aperture radar (SAR) imaging processing because of its easy implementation and high processing efficiency. However, owing to the poor quality of the image produced by RD algorithm, this traditional imaging method is growing increasingly unable to meet practical needs. In an effort to solve the problem of poor azimuth imaging quality, this study proposes a high‐resolution RD azimuth imaging algorithm. The expression of the optimal order of the SAR azimuth signals using fractional Fourier transform (FrFT) is derived in detail herein. A theoretical analysis shows that this optimal order is unique and depends on the azimuth imaging parameters. The experimental results based on airborne SAR simulation data and spaceborne SAR measurement data indicate that the azimuth resolution of the proposed algorithm is improved by 31.6 or 46.8% as against that of the traditional RD algorithm, whereas the peak side lobe ratio (PSLR) and integrated side lobe ratio (ISLR) values obtained via the proposed algorithm are approximately equivalent to those obtained via the traditional RD algorithm.